Metallicity distribution of the progenitor of the Giant Stellar Stream in the Andromeda Galaxy. Issue 2 (29th January 2022) - Milošević, S; Mićić, M; Lewis, G F
ABSTRACT: The Giant Stellar Stream (GSS) is a prominent tidal feature in the halo of the Andromeda galaxy (M31), representing the ongoing destruction of a satellite galaxy. In this paper, we investigate the formation of the GSS through detailed numerical simulations of the tidal disruption of a progenitor system. Assuming that the stream was created in a single merger event between M31 and a dwarf spheroidal galaxy with stellar mass 10^9 M_, we successfully reproduce the dynamical properties of the GSS. As the metallicity distribution along the stream has been well determined from observations (Pan-Andromeda Archaeological Survey and Absorption Maps in the Gas of Andromeda data sets), we use Monte Carlo simulations to reconstruct the original metallicity distribution of the dwarf progenitor. We find that a progenitor dwarf galaxy with a negative radial metallicity gradient, ΔFeH = −0.3 ± 0.2, reproduces the observed GSS properties at a time between 2.4 and 2.9 Gyr into the merger. We also show that the observed double-peak metallicity distribution along the stream is a transitory structure caused by unique merger circumstances where two groups of streaming stars are moving in opposite directions, intersecting to produce the peaks.